2021
DOI: 10.1111/jch.14297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the oral testosterone undecanoate Kyzatrex™ on ambulatory blood pressure in hypogonadal men

Abstract: Testosterone replacement therapies have been shown to increase blood pressure (BP) in hypogonadal men. We studied the effects of a new formulation of testosterone undecanoate (Kyzatrex™) on ambulatory blood pressure (ABP) and heart rate, in 155 men with hypogonadism (mean age, 50.5 years, 76.8% white, 36.1% on antihypertensive therapy). The ABP, heart rate and clinical assessments were obtained at baseline and following 120 and 180 days of therapy. Mean changes from baseline in 24‐h ambulatory systolic BP of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“… 17 Another ambulatory BP study of a developmental oral TU drug with dose titrations reported that the oral TU increased mean ambulatory systolic/diastolic BPs as 1.7 mmHg/0.6 mmHg and 1.8 mmHg/0.6 mmHg for 120 days and 180 days, respectively, in 155 hypogonadal subjects. 20 The mean increases in systolic BP in patients receiving antihypertensive medication were slightly higher (3.4 mmHg) compared to those without anti‐hypertensive therapy (0.7 mmHg). Note that, 3.2% of the oral TU patients were started on new antihypertensive agents during the 180‐day study.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“… 17 Another ambulatory BP study of a developmental oral TU drug with dose titrations reported that the oral TU increased mean ambulatory systolic/diastolic BPs as 1.7 mmHg/0.6 mmHg and 1.8 mmHg/0.6 mmHg for 120 days and 180 days, respectively, in 155 hypogonadal subjects. 20 The mean increases in systolic BP in patients receiving antihypertensive medication were slightly higher (3.4 mmHg) compared to those without anti‐hypertensive therapy (0.7 mmHg). Note that, 3.2% of the oral TU patients were started on new antihypertensive agents during the 180‐day study.…”
Section: Discussionmentioning
confidence: 90%
“…Oral administration of TU has been shown to increase ambulatory blood pressures in previous literature 17,20,21 . The review report of Swerdloff et al.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…В результате у участников исследования с артериальной гипертензией в анамнезе, получавших антигипертензивную терапию, и у пациентов с сахарным диабетом 2 типа наблюдалось большее увеличение как артериального давления, так и частоты сердечных сокращений в амбулаторных условиях на фоне приема тестостерона ундеканоата в дозе от 100 мг один раз в день до 400 мг два раза в день, чем у тех, у кого не было этих 2 сопутствующих заболеваний. У мужчин с гипогонадизмом, которые не получали антигипертензивные препараты, наблюдались незначительные изменения артериального давления и частоты сердечных сокращений [41].…”
Section: какую форму тестостерона выбрать?unclassified